2016
DOI: 10.1111/jfbc.12335
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies on the effect of watercress juice on digestive enzymes relevant to type 2 diabetes and obesity and antioxidant activity

Abstract: Inhibition of enzymes involved in carbohydrate and lipids metabolism is an important strategy against type 2 diabetes and obesity, by suppressing dietary sugar and fat absorption. This work reports, for the first time, the in vitro inhibition of α‐glucosidase, α‐amylase and lipase by watercress juice (WJ). Juice was analyzed for qualitative and quantitative composition and in vitro antioxidant activities. Several components were identified, namely hydroxycinnamic acids, flavonols, and other minor water‐soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
2
20
0
2
Order By: Relevance
“…p-Coumaric acid was identified as the most abundant phenolic compound in the non-stored watercress sample, followed by quercetin-3-O-sophoroside, isorhamnetin-O-hydroxyferuloylhexoside-O-hexoside, isorhamnetin-O-hydroxyferuloylhexoside-O-malonylhexoside, and isorhamnetin-O-sophoroside-O-malonylhexoside. The latter compound was also reported as being dominant in watercress juice by Spínola et al (2016), although those authors identified caffeoylmalic acid, disinapoylgentibiose and ferulic acid as the most abundant phenolics. Grouped flavonoids predominated over phenolic acids and derivatives due to the relatively high levels of isorhamnetin and quercetin glycosides and, in lesser extent, of kaempferol.…”
Section: Effect Of the Postharvest Treatments On The Phenolic Profilementioning
confidence: 98%
See 2 more Smart Citations
“…p-Coumaric acid was identified as the most abundant phenolic compound in the non-stored watercress sample, followed by quercetin-3-O-sophoroside, isorhamnetin-O-hydroxyferuloylhexoside-O-hexoside, isorhamnetin-O-hydroxyferuloylhexoside-O-malonylhexoside, and isorhamnetin-O-sophoroside-O-malonylhexoside. The latter compound was also reported as being dominant in watercress juice by Spínola et al (2016), although those authors identified caffeoylmalic acid, disinapoylgentibiose and ferulic acid as the most abundant phenolics. Grouped flavonoids predominated over phenolic acids and derivatives due to the relatively high levels of isorhamnetin and quercetin glycosides and, in lesser extent, of kaempferol.…”
Section: Effect Of the Postharvest Treatments On The Phenolic Profilementioning
confidence: 98%
“…Up to twenty-six compounds were detected (Table 1), seven of which were phenolic acid derivatives, eighteen flavonoids glycoside derivatives, and one sesquiterpenoid (roseoside). Many of these compounds have already been previously reported in watercress (Martínez-Sánchez, Gil-Izquierdo, Gil, & Ferreres, 2008;Santos et al, 2014;Spínola et al, 2016), so that their identities were assumed; in some of them the fragmentation patterns given by Martínez-Sánchez et al (2008), Santos et al (2014), and Spínola et al (2016) were also used to establish the location of the substituents (e.g., peaks 4 and 8). Nonetheless, to the best of our knowledge, compounds 17 and 23-26 were not previously reported for this species.…”
Section: Characterization Of Phenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The %AA of WE-loaded PCL-PEG nanofibers in the presence of WE, whencompared with %AA of PCL-PEG nanofibers is high. Several scientific studies have been reported antioxidant activity of WE [36][37][38]. Watercress is a medicinal plant with mainly potent complexing activities due to the presence of phenolic and flavonoid compounds and other phytochemicals [39].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Watercress is a medicinal plant with mainly potent complexing activities due to the presence of phenolic and flavonoid compounds and other phytochemicals [39]. Several number of literatures found in the database have shown that the various part of the WE possess antioxidant activity [36][37][38]40]. In a study by Aires and et al [41], phytochemical composition and antioxidant activity of WE was evaluated and it was shown that WE possess high antioxidant capacity and this property was extremely related with quercetin-3-Orutinoside, caffeic acid, isorhamnetin and glucosnastrutiin.…”
Section: Antioxidant Activitymentioning
confidence: 99%